RELATIONSHIP BETWEEN ENVIRONMENTAL FACTORS WITH THE INCIDENCE OF STUNTING IN TODDLERS IN MALAWILI COMMUNITY HEALTH CENTER AND KLAMONO COMMUNITY HEALTH CENTER, SORONG DISTRICT, SOUTHWEST PAPUA (Proceedings OPTIMAL, 2025)
Background: Environmental factors such as sanitation, clean water, and handwashing habits greatly influence the incidence of stunting. The results of this study can serve as a basis for further efforts to improve environmental sanitation and family welfare in Sorong Regency. This study aims to determine the relationship between environmental factors and the incidence of stunting at the Malawili Health Center and Klamono Health Center in Sorong Regency, Southwest Papua Province.Research Methods: This study is a Descriptive Analytic study with a cross-sectional approach. The research population consists of families with stunted toddlers, totaling 60 cases. The research instruments used questionnaires to gather information on clean water sources, latrine ownership, and handwashing habits, utilizing both primary and secondary data collection techniques.Research Results: The statistical test results using Chi-Square obtained values of (p=0.973) for clean water sources, (p=0.829) for latrine ownership, and (p=0.559) for handwashing habits.Conclusion: There is no relationship between clean water sources, latrine ownership, and handwashing habits with the incidence of stunting.